The Limits of Human Knowledge: A Critical Examination of Skepticism and Foundationalism in Epistemology (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
This paper critically examines the limits of human knowledge by analyzing two central epistemological frameworks—skepticism and foundationalism. While skepticism challenges the possibility of certain knowledge, foundationalism seeks to establish indubitable bases for justified belief. Through a close reading of Descartes’ methodological doubt and Hume’s empiricist skepticism, the study explores whether radical skepticism undermines all knowledge claims or whether foundationalist approaches can provide a defensible structure for epistemic justification. The paper further evaluates contemporary responses, including coherentism and reliabilism, to assess their viability in addressing the problem of justification. Ultimately, the research argues that while neither skepticism nor foundationalism alone offers a complete solution, a synthesized approach—incorporating elements of pragmatic and social epistemology—may provide a more robust account of human knowledge.